Cement stabilisation of recycled concrete aggregate modified with polyvinyl alcohol. Issue 2 (28th January 2022) - Yaowarat, Teerasak; Horpibulsuk, Suksun; Arulrajah, Arul; Maghool, Farshid; Mirzababaei, Mehdi; Rashid, Ahmad Safuan A.; Chinkulkijniwat, Avirut
ABSTRACT: During the past few decades, the engineering and geotechnical properties of recycled concrete aggregate (RCA) has been investigated to evaluate its potential to use as a road construction material. This research studied the usage of polyvinyl alcohol (PVA) and cement for improving the mechanical strengths of RCA to be used as an alternative material in pavement base/subbase applications. The results showed that mixing PVA > 1.5% into the cement-stabilised RCA has a vital role in improving the compressive strength along with gaining a higher modulus of toughness. The unconfined compressive strength (UCS) value of stabilised RCA with 3% cement and RCA with 3% cement and 1.5% or 2% PVA met the minimum requirement for 7 days of curing. The addition of PVA reduced the resilient modulus (MR ); however, the MR value of all blends was still higher than the minimum recommended value. The specimens with 28 days of curing had higher resilient modulus values than 7-day cured samples. The CBR value and swelling in soaked condition reduced with increasing the PVA content. The cement-PVA-stabilised RCA, as a supplementary material with up to 1.5% or 2% PVA content and 3% General Portland (GP) were found to have physical and strength properties, which comply with road authority requirements.